The effect of angle between the graft and coronary artery on volumetric flow rate through the anastomosis - S.S. Galych; A.V. Rudenko; E.A. Nastenko; Yu.S. Starodub (Кардіохірургія та інтервенційна кардіологія)
The aim – to determine the optimal value of the angle between the graft and the coronary artery, which can ensure maximum volumetric blood flow through the created coronary anastomosis. Materials and methods. The study was carried out with porcine vessels. Coronary anastomoses were created between grafts and coronary arteries located in porcine myocardium with angles of 30°, 45° and 90°. A total of 81 coronary anastomoses were created – 27 comparison triples. To assess the volumetric blood flow through the coronary anastomosis, the transit-time volume flowmeter was used. A special solution was passed through the graft at constant pressure. This solution was a 7.5 : 7 mixture of distilled water and glycerin to achieve a relative viscosity equal to that of blood – 4.5. All anastomoses compared with each other were created with the same vessels for the purity of the experiment. Anastomoses were also investigated using X-ray contrast imaging in lateral and antero-posterior projections. Using angiography, the internal diameters of the anastomoses were measured. Results. Anastomoses with an angle of 30° and 45° revealed greater values ​​of volumetric blood flow compared with a 90° angle. The results of the X-ray contrast study confirmed an increase in both (longitudinal and transverse) diameters of the anastomoses with an angle of 45°. Conclusions. The angle of 45° is considered to be the most optimal for anastomosis regarding the feasibility and the capacity of those anastomoses to provide higher velocity of blood flow, as well as by increasing the size of the anastomosis, which corrects possible unevenness of the suture line